Water-in-oil-in-water double emulsions as protective carriers for Sambucus nigra l. coloring systems - Teixeira, Liandra Gracher (2022)
The use of natural colorants is needed to overcome consumer concerns regarding synthetic food colorants0 safety. However, natural pigments have, in general, poor stability against environmental stresses such as temperature, ionic strength, moisture, light, and pH, among others. In this work, water-in-oil-in-water (W1/O/W2) emulsions were used as protective carriers to improve color stability of a hydrophilic Sambucus nigra L. extract against pH changes. The chemical system comprised water and corn oil as the aqueous and oil phases, respectively, and polyglycerol polyricinoleate (PGPR), Tween 80, and gum Arabic as stabilizers. The primary emulsion was prepared using aW1/O ratio of 40/60 (v/v). For the secondary emulsion,W1/O/W2, different (W1/O)/W2 ratios were tested with the 50/50 (v/v) formulation presenting the best stability, being selected as the coloring system to test in food matrices of different pH: natural yogurt (pH 4.65), rice drink (pH 6.01), cow milk (pH 6.47), and soy drink (pH 7.92). Compared to the direct use of the extract, the double emulsion solution gave rise to higher color stability with pH change and storage time, as corroborated by visual and statistical analysis.